PENGARUH KUALITAS PRODUK HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA KERAJINAN KERANG UD KERANG MURAH JAYA PANARUKAN KABUPATEN SITUBONDO - Ediyanto, Ediyanto; Minullah, Minullah (Growth, 2022)
His study aims (1) To determine the partial effect of product quality variables (X1), price (X2) and location (X3) on consumer satisfaction (Y). (2) To determine the simultaneous influence of product quality variables (X1), price (X2) and location (X3) on consumer satisfaction (Y). (3) To find out among the product quality variables (X1), price (X2) and location (X3) that have a dominant influence on customer satisfaction (Y). Data collection techniques used Observation, Interview, Questionnaire, and Literature Study. Data Analysis Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, Dominant Test and Determination Coefficient Test. The results of the study are the equation of multiple linear regression Y = 3,716E-17 + 0,683X1 + 0,226X2 + 0,003X3 + e. Partially, product quality has a significant positive effect with tcount greater than t table 10.035> t table 1.986 or sig 0.000 <0.050, the price indicates a value of 3.319> t table 1.986 or sig 0.001 <0.050 location indicates a value of 0.053 <t table 1.986 or sing 0.958> 0.050. F test is known to know that Fcount 49.070> Ftable 2.70 and a significant value of F 0.000 <0.050, then Ho is rejected and Ha is accepted. The dominant influential variable is product quality received.